Two remarks on the Bâtiment Nord of the Sanctuary of Baalshamin in Palmyra (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
The Bâtiment Nord of the Sanctuary of Baalshamin in Palmyra was excavated by a Swiss team led by Paul Collart in 1956. The excavation revealed the remains of a building that was in use from the 1st century AD until its demise in the early Islamic period. This contribution will examine the original documentation of the excavations in the Fonds d’Archives Paul Collart at the University of Lausanne. It will advance the possibility that the Bâtiment Nord in the Roman period might have been more extensive than what was previously thought by Collart and his team and will provide the reader with a brief overview of some of the post-Classical remains in this compound. In so doing, this contribution will present the unpublished results of a sondage conducted to the north of the modern Hotel Zenobia.
Keywords: Palmyra; Bâtiment Nord; Sanctuary of Baalshamin; late antiquity; early Islamic period; Paul Collart